Synthesis of novel drug-free cancer targeting nanotherapeutics - Cheong, How Min (Nanyang Technological University, 2020)
Cancer remains the leading cause of death worldwide. Mesoporous silica nanoparticles (MSNs) are seen as one of the promising candidates for anti-cancer therapy, due to its favourable cancer-killing properties. In this research paper, MSNs are being further modified, through attachment of PEG (Polyethylene Glycol) chains, in efforts to increase its ability to cause cancer cell death in-vivo, by reducing aggregation and therefore increasing the stability of MSNs. Preliminary in vitro results indicate that PEG conjugation can significantly enhance the stability of MSN in water as well as physiologically-emulated phosphate-buffered saline (PBS). These data lay a solid foundation for the follow-up fabrication of cancer-targeting physiologically-stable silica nanomedicine.